Literasi Mitigasi Risiko dan Asuransi Perjalanan Wisata - Kurniawan, Yohanes Jhony; Julianto, Heppy; Suhartono (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
This Community Service Takes the Title of Risk Mitigation Literacy and Travel Insurance. This Community Service aims to produce PKM Outcome Materials that will be published in Premium journals or journals of community service and entrepreneurship, Risk Mitigation Literacy Materials and travel insurance made in, zoom recordings, and disseminate via YouTube, and Increase literacy to the public through Management Sharing Sessions, posters and expansion of the idea of ​​Risk Mitigation, Travel Insurance, and the importance of understanding the underwriting process in insurance coverage. The method of this research is Implementation Time. The implementation time of the activity is April - August 2022. In the form of designing Literacy Materials for Risk Mitigation and Travel Insurance, publishing the idea of ​​Risk Mitigation and Travel Insurance, and conducting literacy by holding Zoom meetings in Management Sharing Sessions activities underwriting process insurance coverage. The result of this Community Service is the availability of literacy materials, posters, literacy activities in the 7.08th Management Session.